"VACCINATION" BY STRESS IN PHYSICAL PREPARATION OF PROFESSIONAL SOLDIERS - Roman MARKOVIČ; Jaromír ŠIMONEK (Cluj University Press, 2020)
Introduction. This article deals with the issue of the use of "vaccination" techniques using stress in the physical training of professional soldiers. In the practice of a military professional, exposure to stressors is a common phenomenon, so it is important in the physical training of professionals to include in exercise programs training means to increase adaptation to stress. Results. The professional article contains a description of the issue of the influence of stressors on the performance of professional soldiers, adaptation, response to stress and proposals for individual training methods to increase stress tolerance.